Nilai-Nilai Pendidikan Akhlak Melalui Syair Islami - Ariyanda IL (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
This study examines the moral values ​​contained in the text of the song Rafly Kande. This research is a qualitative research. The method used in this research is descriptive qualitative analysis. The data in this study is the value of moral education in the text of Rafly's song entitled Wasiet Keu Aneuk, Gisa Bak Punca and Jasa Poma. the results obtained in the form of Moral Education Values ​​in Rafli's song lyrics are as follows: (a). In the song Wasieut Keu Aneuk there is the value of moral education towards Allah and the Apostle, then Moral Education towards Parents and Moral Education towards others. (b). Then in the Song of Gisa Bak Punca there are values ​​of moral education to Allah and His Messenger, to oneself, the value of moral education to parents and the value of moral education to the social environment. (c). While in the lyrics of the song Jasa Poma there is only the value of moral education for parents, especially mothers. As for the views of academic figures, musicians, politicians and activists, it is stated that in the lyrics of Rafli's songs there are many values ​​of moral and moral education in them, some of which most often appear are: Moral Education Values ​​to Allah and His Apostle, Values Moral Education to Parents, Moral Education Value to oneself, and Moral Education Value to the social environment (society).